Future of Health Technology : Future of Health Technology. - Bushko, R. G. (Studies in health technology and informatics., 2002)
Health technology has become the centre of healthcare systems strategic planning process. Developing a clear vision of the future of health technology and smart investment in technology are the critical success factors. Healthcare executives need to develop a vision of future health technology to lead effectively in the 21st century. ""Future of Health Technology"" helps to develop a clear vision of the future and it assists in planning of investments in health technology for those involved in setting health systems strategy for the 21st century. This book provides a comprehensive vision of th.